Indira Viswanathan Peterson, Poems to Shiva, The Hymns of the Tamil Saints, New Jersey, Princeton University Press, 1989, 382 pp. (Ilustraciones.) (Princeton Library of Asian Translations.) - Duque-Saberi, Isabel A. (Estudios de Asia y África, 1991)
-